Metafora Konseptual terkait Penyakit dalam Bahasa Karo - Sembiring, Gunawan; Mulyadi, Mulyadi; Nurlela, Nurlela (Jurnal Bahasa dan Sastra, 2024)
This research discusses conceptual metaphors related to diseases in Karo language. The purpose of this research is to know and describe the use of conceptual metaphors related to diseases in Karo language. The data source is taken from the expression of disease in Karo language. The research method used is descriptive qualitative method with cognitive semantic approach. The theory of conceptual metaphor according to Lakoff and Johnson (1980) is used as a reference to analyze the data. Based on the results of the analysis, there are three types of conceptual metaphors in Karo language, namely; structural metaphors with the meaning concepts of enemy and struggle with the image scheme of power; orientational metaphors with the meaning concepts of anger and achievement with the image scheme of space and; ontological metaphors with the meaning concepts of explosion, expansion, growth, effort, disappointment, and travel with the image scheme of existence and identity.